AN ANALYSIS OF STUDENT’S PROBLEMS IN SPEAKING AT ELEVENTH GRADE OF SMA NEGERI 1 SUKODADI - Turada, Alfi Syahidah (E-Link Journal, 2021)
Student usually faced several problems when speaking, such as lack of vocabulary and grammar. This research is focus on speaking skill as important skill of four basic language learning.  Using qualitative descriptive method, researcher analysis students' problems in speaking of eleventh grade students in SMA Negeri 1 Sukodadi, Lamongan.  The students’ usually faced problems when speaking, such as lack of vocabulary and grammar. This research is guided by research problems as follows: (1) what are student’s problems in speaking English at eleventh grade in SMA Negeri 1 Sukodadi. (2) What are the causes of students’ problems in speaking English at eleventh grade in SMA Negeri 1 Sukodadi. Researcher used qualitative methods. In answering research problems, researcher used observations and interviews. The researcher uses three main phases of data analysis namely data reduction, data display, and drawing conclusions. Based on the data analysis, the result of research found the students problems, included the cause of problems in English speaking. In speaking English every students has their typical problems, but in general those can be stated as follows: lack of vocabularies, grammar, pronoun, comprehension and fluency. The researcher also found that the causes of students’ problems are, lack of confidence, fear of mistakes, shyness, anxiety and low of motivation.  Keywords: Student’s problem, speaking